2020
DOI: 10.18502/keg.v5i4.6800
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Basalt Fiber Reinforced Fly Ash-Based Geopolymer Composites

Abstract: This article analyses the influence of a short basalt fibre admixture on the mechanical properties of geopolymers, especially compressive strength. This preliminary research is the first step towards the development of a composite for fire resistant applications in civil engineering. This study investigates the behaviour of a fly ash based geopolymer containing basalt fibres. Fly ash from the coal power plant ‘Skawina’ (located in: Skawina, Lesser Poland, Poland) was used as the raw material. The chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…This behaviour was the same for all curing methods. The change of the behaviour is coherent with the research reported in the literature [29][30][31][32].…”
Section: Mechanical Properties -Compressive Strengthsupporting
confidence: 91%
See 4 more Smart Citations
“…This behaviour was the same for all curing methods. The change of the behaviour is coherent with the research reported in the literature [29][30][31][32].…”
Section: Mechanical Properties -Compressive Strengthsupporting
confidence: 91%
“…Preliminary observations confirm the regular distribution and coherency of fibres and the geopolymer matrix [29]. The SEM investigations enabled familiarisation with the overall structure of the composites and the role of fibres.…”
Section: Microstructure Investigationsupporting
confidence: 57%
See 3 more Smart Citations